Lembaga Perlindungan Saksi dan Korban Sebagai Leader Sector dalam Memenuhi Hak Korban Tindak Pidana Terorisme di Indonesia - Kurnia, Rizky (Southeast Asian Journal of Victimology, 2023)
Criminal acts of terrorism cause material and immaterial losses. Victims of criminal acts of terrorism need protection and restoration of their rights, therefore Indonesia has an institution authorized to protect witnesses and/or victims so that the protection and restoration of the rights of victims, one of which is the rights of victims of criminal acts of terrorism, can be fulfilled. The problems studied in this study are regarding the implementation of witness and victim protection institutions (LPSK) in fulfilling the rights of victims of criminal acts of terrorism in the Indonesian criminal justice system, and regarding mechanisms for fulfilling the rights of victims of criminal acts of terrorism. This research was conducted using normative juridical methods. The research approach uses a statutory approach. The data source used in this study is a secondary data source which is then analyzed qualitatively. The LPSK mechanism in fulfilling the rights of victims of criminal acts of terrorism is inseparable from the role of the victim who must play an active role in submitting a request to the head of the LPSK. The application can be submitted by the victim, his family or his attorney.